2008
DOI: 10.1208/s12249-007-9031-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Buccoadhesive Controlled Release Tablets of Lercanidipine

Abstract: The purpose of this research was to develop and evaluate buccal mucoadhesive controlled release tablets of lercanidipine hydrochloride using polyethylene oxide and different viscosity grades of hydroxypropyl methylcellulose individually and in combination. Effect of polymer type, proportion and combination was studied on the drug release rate, release mechanism and mucoadhesive strength of the prepared formulations. Buccal mucoadhesive tablets were made by direct compression and were characterized for content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…In vitro drug release studies were performed using in-house modified USP type-I dissolution apparatus as reported earlier (Charde et al, 2008, Jaipal et al, 2013. Briefly, the method uses 50 mL capacity screw cap tubes arranged on a dissolution vessel using in-house designed aluminum holder.…”
Section: Drug Contentmentioning
confidence: 99%
“…In vitro drug release studies were performed using in-house modified USP type-I dissolution apparatus as reported earlier (Charde et al, 2008, Jaipal et al, 2013. Briefly, the method uses 50 mL capacity screw cap tubes arranged on a dissolution vessel using in-house designed aluminum holder.…”
Section: Drug Contentmentioning
confidence: 99%
“…Formulations were chosen, from each of the constructed phase diagram of nanoemulsifying region so obtained, such that amount of oil in each formulation should be able to dissolve 10 mg of drug easily as recommended dose of LER is 10 mg/day Charde et al [12].…”
Section: Selection Of Combination (Nli or Nlii)mentioning
confidence: 99%
“…Rabbits fasted for 24 h before the experiment and were divided into two groups, each having six animals. The selection of rabbits as animal model for the present study was based on previously published pharmacokinetic studies (31)(32)(33). The first group received orally the 10-mg reference tablets (Zyprexa® by Eli Lilly) and the second group received orally 10-mg CR test tablets of olanzapine.…”
Section: In Vivo Evaluationmentioning
confidence: 99%